2018
DOI: 10.1155/2018/7617685
|View full text |Cite
|
Sign up to set email alerts
|

Chemocatalytic Production of Lactates from Biomass-Derived Sugars

Abstract: In recent decades, a great deal of attention has been paid to the exploration of alternative and sustainable resources to produce biofuels and valuable chemicals, with aims of reducing the reliance on depleting confined fossil resources and alleviating serious economic and environmental issues. In line with this, lignocellulosic biomass-derived lactic acid (LA, 2-hydroxypropanoic acid), to be identified as an important biomass-derived commodity chemical, has found wide applications in food, pharmaceuticals, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…These results are consistent with those obtained in acidity assessment and could be explained with the notably differences in amount, density and strength of acid sites observed (Section 3.1). As reported in numerous works [27,32,55],…”
Section: Catalytic Performancementioning
confidence: 69%
“…These results are consistent with those obtained in acidity assessment and could be explained with the notably differences in amount, density and strength of acid sites observed (Section 3.1). As reported in numerous works [27,32,55],…”
Section: Catalytic Performancementioning
confidence: 69%
“…(2) the (HEIm) 2 ZnBr 2 was incorporated into MPR by alkoxylation. Under the reaction temperature of 140℃ for 6 h, 72.3% selectivity of GC was achieved using (HEIm) 2 [113] (La) based catalysts were also developed in the synthesis of GC, including LaCl 3 [123], La 2 O 3 [124], and La 2 Cu 0.5 Fe 0.5 O 4 [125]. For LaCl 3 catalyzed glycerolysis, the key reaction mechanism is illustrated in Scheme 11. ree oxygen atoms of the carbonyl group of the 2,3-dihydroxypropyl carbamate (HPC) coordinated with La 3+ of LaCl 3 ; the electrons of C-N groups redistributed wherein the proton transferred onto the carbon atom leading to the carbocation and nitrogen anion and favoring the intramolecular nucleophilic attack of adjoining hydroxyl group.…”
Section: Reaction With Tungsten-based Catalyst Inmentioning
confidence: 99%
“…Modern life depends on polymers, from materials applied in the manufacture of clothing, houses, cars, and airplanes to those demonstrating complex adhibitions in medicine, diagnostics, and electronics [1][2][3][4]. A vast majority of polymers have been contributing greatly to our better daily life of enhanced quality and cleaner living environments, for instance, as materials capable of purifying water or as polymers bearing the better fuel economy in aerospace utilizations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HMF can be further degraded to formic and levulinic acids [21]. On the other hand, alkaline medium or catalysts containing Lewis acidic sites promote sugars isomerization to their corresponding ketoses, such as xylulose, ribulose and fructose [26,27]. Ketoses undergo retro-aldol condensation, in which C-C bonds are cleaved, leaving the formation of 2-and 3-carbon compounds, like glycolaldehyde and trioses: glyceraldehyde and dihydroxyacetone (DHA) [28].…”
Section: Introductionmentioning
confidence: 99%
“…The research found in literature showed that LA production by hydrothermal conversion of saccharides is achieved using homogeneous or heterogeneous acid and base catalysts [27]. Reasonable yields to LA were obtained under alkaline hydrothermal conditions from glucose for short reaction times [35,36].…”
Section: Introductionmentioning
confidence: 99%